A study to assess global availability of fetal surgery for myelomeningocele. (20th November 2018) - Sacco, Adalina; Simpson, Lynn; Deprest, Jan; David, Anna L.
Abstract: Aim: To establish the provision of fetal surgery for myelomeningocele (MMC) worldwide. Methods: Through the International Society for Prenatal Diagnosis (ISPD) Fetal Therapy Special Interest Group and the North American Fetal Therapy Network (NAFTNet), fetal therapy centres were surveyed (September 2017‐June 2018) regarding availability of fetal MMC surgical repair, patient inclusion criteria, repair techniques, number of cases, and outcome reporting. Responses were summarised on an interactive map on the ISPD website. Results: Forty‐four of 59 centres responded (74.6%) of which 34 centres (77.1%) currently offered fetal surgery for MMC and seven centres (15.9%) were awaiting a first case after service set up. Patient inclusion criteria were similar and based on the Management of Myelomeningocele (MOMS) trial. Five centres (14.7%) operated beyond 26 weeks' gestational age, outside the MOMS criteria. Open fetal surgery was provided in 23 centres (67.6%), fetoscopic surgery only in five (14.7%), and six centres offered both types (17.6%). Neurosurgical closure was similar for open surgery but highly variable in fetoscopy surgery. The median number of cases per centre was 21 (range 1‐253). Conclusions: Fetal surgery for MMC is now offered globally. Two thirds of centres offer open repair via hysterotomy using criteria based on the MOMS trial. Abstract : What's already known about this topic? The Management of Myelomeningocele Study (MOMS trial) provided level 1 evidence that fetal surgery for myelomeningocele (MMC) improved neonatal outcome compared with postnatal surgery. Provision of fetal surgery has expanded since the MOMS trial, but it is unclear how many centres offer fetal MMC closure. Various closure techniques have been described, particularly for fetoscopic surgery. Case series suggest a broadening of inclusion criteria from those used in the MOMS trial. What does this study add? This study provides a global resource of centres offering fetal surgery for MMC and details of their service. Two thirds of centres perform this operation by hysterotomy and the vast majority with patient inclusion criteria based on the level 1 RCT evidence (the MOMS trial). A few centres now offer surgery up to 28 weeks of gestation, beyond the MOMS trial inclusion criteria. Neurosurgical closure was similar for open surgery but highly variable between centres offering fetoscopy surgery; more data is needed regarding the optimal type of fetoscopic repair and its comparison to open surgery.